Contrast-enhanced ultrasound and microwave ablation of Epstein–Barr virus associated smooth muscle tumors in a patient with AIDS: a case report - Yang, Yuanping; Bai, Xiumei; Wu, Yuquan; Yang, Hong; He, Yun (Frontiers in Medicine, 2024)
This case report presents a rare case regarding the contrast-enhanced ultrasound (CEUS) features and minimally invasive treatment of Epstein–Barr virus associated smooth muscle tumors (EBV-SMT) in a patient with human immunodeficiency virus infection (HIV). Currently, there are few studies involving hepatic EBV-SMT. According to WHO guidelines, the malignant potential of the disease is uncertain. The features of CEUS suggest that these hepatic lesions tend to be malignant and are often misdiagnosed as other malignant neoplasms. Presently, hepatic resection is the first choice for treating hepatic EBV-SMT. However, immunocompromised patients may benefit more from minimally invasive microwave ablation therapy (MWA). Since there is no standard diagnosis and therapy are available at present, our findings in this case may contribute to promoting standardized diagnosis and treatment of EBV-SMT.